Duplication cyst of ascending colon presenting as an ileal volvulus in a child: A case report and review of literature - Adesoji O Ademuyiwa; Christopher O Bode; Opeoluwa A Adesanya; Olumide A Elebute (Wolters Kluwer Medknow Publications, 2012)
Alimentary tract duplications are uncommon congenital anomalies that may be found anywhere along the gastrointestinal tract. They have a diverse presentation and often times present with complications of intestinal obstruction and/or lower gastrointestinal haemorrhage. We report a very rare finding of a colonic duplication cyst which presented as an ileal volvulus in a young girl. While available investigations were non-specific, the child survived on account of an early decision to operate. She had resection of the duplication cyst and ileo-colic anastomosis. She made good recovery post-operatively. A high index of suspicion is necessary on the part of clinicians to recognise this condition. Early operative intervention is necessary in the developing world setting where state of the art investigations are not available for accurate pre-operative diagnosis.